2021
DOI: 10.3390/antibiotics10030318
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Antibacterial Activities and Mechanisms of Natural Alkaloids: A Review

Abstract: Alkaloids are nitrogen-containing heterocyclic compounds typically isolated from plants. They represent one of the most important types of natural products because of their large number and structural diversity and complexity. Based on their chemical core structures, alkaloids are classified as isoquinolines, quinolines, indoles, piperidine alkaloids, etc. In-depth analyses of alkaloids have revealed their antibacterial activities. To date, due to the widespread use of antibiotics, the problem of drug-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 111 publications
(87 reference statements)
5
77
0
3
Order By: Relevance
“…Natural phenolic compounds, including curcumin and rosmarinic acid with antibiofilm and anti-QS properties have been described (Rasamiravaka et al 2015). Plants contain antibiofilm and anti-efflux pump compounds, including alkaloids (Rasamiravaka et al 2015;Yan et al 2021). Alkaloids are potentially active against various bacterial strains, including drug-resistant ones (Yan et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Natural phenolic compounds, including curcumin and rosmarinic acid with antibiofilm and anti-QS properties have been described (Rasamiravaka et al 2015). Plants contain antibiofilm and anti-efflux pump compounds, including alkaloids (Rasamiravaka et al 2015;Yan et al 2021). Alkaloids are potentially active against various bacterial strains, including drug-resistant ones (Yan et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Since dehydrocorydaline was a major component with the strongest antibacterial activity among the C. turtschaninovii constituents, it was used to further study its potential antibacterial mechanisms of action against L. monocytogenes . Isoquinoline alkaloids have been studied for their antibacterial mechanisms with respect to their distinctive chemical structures such as inhibition of bacterial nucleic acid synthesis and metabolism, interference with cell membrane transporters, suppression of cell division, and disruption of cell membrane, leading to bacterial cell lysis ( Cushnie et al, 2014 ; Yan et al, 2021 ). These studies agree with our results, indicating that L. monocytogenes cells treated with dehydrocorydaline showed morphological and intracellular structural changes such as disappearance of cell walls, membrane destruction, and leakage of intracellular components in TEM observation ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their antibacterial activities have been proven, and many studies have reported that they can play a significant role in treating infectious diseases. Their mechanism of action might be due to the enzymatic alterations affecting physiological processes, including inhibition of DNA synthesis and repair mechanisms by intercalating nucleic acids [ 9 , 56 , 57 ]. Isoquinolines, aporphines, quinolones, and phenanthrenes are the most critical alkaloid groups with suitable antibacterial activities [ 35 ].…”
Section: Mechanistic Insights On Phytochemicalsmentioning
confidence: 99%